Situação da saúde reprodutiva de mulheres em idade fértil e seus determinantes em uma comunidade urbana de baixa renda do município de Fortaleza, Ceará - Falcão, Germana Benevides (2012)
Cervical cancer screening and family planning are relevant preventive health practices for women of childbearing age. Primary care still privileges gestational period and cervical neoplasia prevention over family planning. Nevertheless, despite improvements on the coverage for cervicovaginal cytology, cervical neoplasia mortality rates show only slight decrease. High rates of teenage pregnancy, abortions and health iniquities persist. The project aimed to portrait the reproductive health situation of childbearing aged women from a low income urban community in Fortaleza, prioritizing cytology procedures and the use of contraceptive methods. This was a cross-sectional study carried out through home interviews with 244 women from the age of 13 to 52 years old. The initial exploratory analysis allowed establishing correlations through the chi-square test for nominal variables and ANOVA for means and standard deviations. Odds ratios as expressions of prevalence ratios were obtained to express the magnitude of the associations using simple and multiple logistic regression. Amongst sexually active women and aged 25 years or more, 90.3% underwent cytology at least every 3 years, and 59.3% did it annually. Cytology annual frequency positively correlated to remunerated employment (OR=2.63; IC95%: 1.49-4.64) and to the condition of having had the maximum of one pregnancy (OR=2.60; IC95%: 1.11-6.08). Regarding family planning, just over half of women (51.9%) used any contraception and 39.5% of them were not guided by doctors or nurses. Oral contraceptives (40.4%) and condom (28.7%) predominated as current contraceptive methods. Family income of R$ 800.00 or above positively correlated with contraception guided by an appropriate professional (OR=3.3, IC95%: 1.28-8.54) and negatively correlated to a history of previous abortion (OR=0.32, IC95%: 0.13-0.82). High rates of cervicovaginal cytology were observed, even annually and out of the age group suggested by the Health Ministry. There was a low rate of contraception, insufficient offer as to methods variety and a high proportion of women who did not received adequate guidance on the use of contraceptive methods. Family income and previous abortion were associated to family planning guided by a qualified professional, whilst remunerated employment and having had the maximum of one pregnancy were associated to annual cytology screening to prevent cervix neoplasia.